The impact of sea ice melt on the evolution of surface pCO2 in a polar ocean basin - Yang, Wei; Zhao, Yu; Wu, Yingxu; Chen, Zijie; Gao, Xiang; Lin, Hongmei; Ouyang, Zhangxian; Cai, Weijun; Chen, Liqi; Qi, Di (Frontiers in Marine Science, 2024)
The strong CO2 sink in Arctic Ocean plays a significant role in the global carbon budget. As a high-latitude oceanic ecosystem, the features of sea surface pCO2 and air-sea CO2 flux are significantly influenced by sea ice melt; however, our understanding of pCO2 evolution during sea ice melt remains limited. In this study, we investigate the dynamics of pCO2 during the progression of sea ice melt in the western Arctic Ocean based on data from two cruises conducted in 2010 and 2012. Our findings reveal substantial spatiotemporal variability in surface pCO2 on the Chukchi Sea shelf and Canada Basin, with a boundary along the shelf breaks at depths of 250-500 m isobaths. On the Chukchi Sea shelf, strong biological consumption dominates pCO2 variability. Moreover, in Canada Basin, the pCO2 dynamics are modulated by various processes. During the active sea ice melt stage before sea ice concentration decreases to 15%, biological production through photosynthetic processes and dilution of ice melt water lead to a reduction in DIC concentration and subsequent decline in pCO2. Further, these effects are counteracted by the air-sea CO2 exchange at the sea surface which tends to increase seawater DIC and subsequently elevate surface pCO2. Compared to the pCO2 reduction resulting from biological production and dilution effects, the contribution of air-sea CO2 exchange is significantly lower. The combined effects of these factors have a significant impact on reducing pCO2 during this stage. Conversely, during the post sea ice melt stage, an increase in pCO2 resulting from high temperatures and air-sea CO2 exchange outweighs its decrease caused by biological production. Their combined effects result in a prevailing increase in sea surface pCO2. We argue that enhanced air-sea CO2 uptake under high wind speeds also contributes to the high sea surface pCO2 observed in 2012, during both active sea ice melt stage and post sea ice melt stage. The present study reports, for the first time, the carbonate dynamics and pCO2 controlling processes during the active sea ice melt stage. These findings have implications for accurate estimation of air-sea CO2 fluxes and improved modeling simulations within the Arctic Ocean.